2021
DOI: 10.7150/ijbs.54055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterization of HSPA5 (GRP78) expression profiles in normal individuals and cancer patients with COVID-19

Abstract: HSPA5 (BiP, GRP78) has been reported as a potential host-cell receptor for SARS-Cov-2, but its expression profiles on different tissues including tumors, its susceptibility to SARS-Cov-2 virus and severity of its adverse effects on malignant patients are unclear. In the current study, HSPA5 has been found to be expressed ubiquitously in normal tissues and significantly increased in 14 of 31 types of cancer tissues. In lung cancer, mRNA levels of HSPA5 were 253-fold increase than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 114 publications
(58 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, recent studies found that TQ might have inhibitory potential against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) protease ( 29 ), particularly for cancer patients ( 30 ). As we know, novel virus SARS-CoV-2 causes coronavirus disease 2019 (COVID-19), and the World Health Organization (WHO) declared COVID-19 as a global pandemic as earlier of March 11, 2020 ( 31 – 33 ). As of the March 22, 2021, the total confirmed cases are 123,719,955, and death cases are 2,724,465 worldwide from the report of Johns Hopkins University ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies found that TQ might have inhibitory potential against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) protease ( 29 ), particularly for cancer patients ( 30 ). As we know, novel virus SARS-CoV-2 causes coronavirus disease 2019 (COVID-19), and the World Health Organization (WHO) declared COVID-19 as a global pandemic as earlier of March 11, 2020 ( 31 – 33 ). As of the March 22, 2021, the total confirmed cases are 123,719,955, and death cases are 2,724,465 worldwide from the report of Johns Hopkins University ( ).…”
Section: Discussionmentioning
confidence: 99%
“…During SARS-CoV-2 infection, the viral spike glycoprotein triggers the endoplasmic reticulum stress [ERS] and stimulates the synthesis of GRP78 [ 51 ]. A prospective case control study reveals that the serum GRP78 was 5 times higher in COVID-19 as compared to the control group [ 52 , 53 ]. Furthermore, studies have demonstrated that the SARS-CoV-2 virus also uses the same GRP78 for its internalization into the host cells [ 51 ].…”
Section: The Viral Modulation Of Iron Metabolism—role Of Ferritin Viral Mimicry Of Hepcidin and ‘Endothelitis’mentioning
confidence: 99%
“…TDP-43102-269 and TDP-431-102 were obtained as previously described 31,32 . The TDP-43 expression strain was described previously 37,38 . The Hsc70.3-WT or Hsc70.3 K97S Drosophila strains were obtained from the Bloomington Drosophila stock center, Indiana, USA.…”
Section: Methodsmentioning
confidence: 99%
“…HspA8 is well described for its implication in nuclear import of client proteins as it shuttles between the cytoplasm and nucleus 36 . Although HspA5 is mostly known for its ER localization, several studies have shown the presence of HspA5 in the nucleus 33,37,38 , including in SH-SY5Y cells 39 . Thus, our data suggest that in the SH-SY5Y cells and in the absence of stress, HspA5 and HspA8 selectively associate with nuclear but not cytoplasmic, TDP-43.…”
Section: Bioid Identifies Hsp70 Network Binding To Tdp-43 In the Nucleusmentioning
confidence: 99%